Un Sermon prêché durant des intempéries, témoin négligé de versets d’Isaïe en vieille-latine - Dolbeau, François (Revue d'études augustiniennes et patristiques, 2013)
Critical edition of an anonymous sermon, present in three manuscrits written in North-Eastern France (the two oldest dating from the end of the ninth century). During a time of very bad weather, the preacher explains that the social urban disorder (oppression by the rich, dispossession of legal heirs) has caused this divine punishment. His biblical arguments depend on Old-Latin Translations, mainly five Isaiah-verses quoted continuously. His language is characterized by many Late Latin phenomena. Most probably, the sermon was preached between 450 and 650 by a talented orator, in one of the biggest Italian cities.